Adrenal Myelolipoma Masquerading as an Adrenal Malignancy. (17th January 2022) - Robinson, Davida A.; Kemeny, Margaret; Muchinyi, Juliana E.; Yasin, Madiha; Montes, Nilda I.; Tuli, Sandeep; Jaiswal, Radhika; Carter, Amanda; Derezil, Michal-Ann; Jang, Hanna; Reich, David
Abstract : An adrenal myelolipoma presenting with suspicious features may pose a diagnostic challenge to surgeons and endocrinologists. In this case report of an adult patient with undiagnosed congenital adrenal hyperplasia presenting with bilateral adrenal masses, we review his radiographic and clinical findings which were highly suspicious for adrenal malignancy. Features of adrenal myelolipoma that may resemble malignant lesions are reviewed. This case report highlights important features of adrenal myelolipoma that the surgeon and endocrinologist should be aware of. The importance of avoiding overtreating adrenal myelolipomas presenting as tumors of uncertain malignant potential is crucial.